Strategi Peningkatan Performa Wasit di Asosiasi Pssi Kota Cimahi - Mubarok, Irfan; Husdarta, J.S; Syamsudar, Bangbang (Jurnal Ilmiah Wahana Pendidikan, 2024)
The background of this thesis is that the performance of a referee is an inseparable part of a match, the good and bad of a match can be seen from the quality of the performance of the match officials who run it. Good referee performance is expected to give the best performance by players. Performance as a record produced on a particular job or activity over a period of time. "Referees are people who lead the course of a sports match. Therefore referees must be equipped with knowledge about the applicable rules of the game and authoritative performances while on the field. This research is a qualitative descriptive study. In this study the authors took the population, namely members soccer referees at the PSSI Association of Cimahi City, totaling 20 people. The sampling technique in this study used an incidental sampling technique. The samples taken in this study were members of the soccer referees at the PSSI Association of Cimahi City, totaling 10 people. The data were obtained by interview and observation through a visual video test for the category of violations in a match and a physical test in the form of Referee Fitness Test-2. Based on the results of the research and discussion it can be concluded that based on the results of the visual video test for the categories of violations in a match and interviews with the referees as a whole football referees at the City PSSI Association Cimahi is already able to analyze a violation and the category of violation so that it is able to make firm decisions in giving violations and cards. While the results of the physical test in the form of Referee Fitness Test-2 to the referees showed that 7 students (70%) passed because they were able to complete the test as a whole and 3 people (30%) failed because they were unable to complete the test as a whole.